COMPANY NETWORKS IN MARITIME CLUSTERS : Case One Sea - Rikkilä, Antti (My University, 2019)
Companies located in a maritime cluster have all their own networks that are comprised of various stakeholders. Nevertheless, the recent studies about maritime clusters have highlighted the importance of external networks that reach outside the cluster. The maritime industry is continuously developing and so must the maritime companies if they want to remain competitive. The purpose of this study was to investigate what relationships companies have to other companies and stakeholders. The main research object of this study was how companies in maritime clusters are networked. This study focused on describing and understanding these networks. To comprehend these networks better, it is important to understand how different maritime companies perceive their collaborative actions, what goals do they have, and how they see the future needs. In this study, the participants were selected based on their involvement in One Sea project. One Sea project suited well as a framework for participant selection because the involved companies represent different sectors in maritime business and therefore, it can give a better view of the maritime industry. The research data in this study was gathered from semi-structured interviews. The findings mostly aligned with theory as similarities to the previous research findings were found. Also, the findings suggest that digitalization and new technologies are promoting new forms of cooperation. The findings identified that companies in maritime clusters seem to be networked in multiple sectors. The networks consisted of both local and global partners. Companies’ reasons for cooperation can be based on common interests, new knowledge or resources. However, potential new partners must meet certain requirements. Even direct competitors can cooperate if their interests are aligned. It can be seen that the developing requirements of maritime industry seem to be promoting the formation of new networks and partnerships that match the future needs. This will highlight the importance of networks with the right capabilities in the future.
Keywords: maritime clusters, networks, maritime industry